2020
DOI: 10.1038/s41598-020-68060-9
|View full text |Cite
|
Sign up to set email alerts
|

HIV X4 Variants Increase Arachidonate 5-Lipoxygenase in the Pulmonary Microenvironment and are associated with Pulmonary Arterial Hypertension

Abstract: Pulmonary Arterial Hypertension (PAH) is overrepresented in People Living with Human Immunodeficiency Virus (PLWH). HIV protein gp120 plays a key role in the pathogenesis of HIV-PAH. Genetic changes in HIV gp120 determine viral interactions with chemokine receptors; specifically, HIV-X4 viruses interact with CXCR4 while HIV-R5 interact with CCR5 co-receptors. Herein, we leveraged banked samples from patients enrolled in the NIH Lung HIV studies and used bioinformatic analyses to investigate whether signature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Among the HIV-1 patients, the R5 (CCR5-tropic) HIV-1 variants predominate over the course of infection, and the X4 (CXCR4-tropic) variants arise later ( Poon et al., 2012 ); however, nearly 22% of patients on cART principally harbor the X4 variants ( Ferrer et al., 2014 ). Moreover, a recent study indicated that X4 variants are mainly associated with pulmonary arterial hypertension—a lung condition quite prevalent among PLWH ( Almodovar et al., 2020 ). Most importantly, NHBEs explicitly express CXCR4 ( Eddleston et al., 2002 ; Gundavarapu et al., 2013 ), and the X4- but not the R5-tropic HIV-gp120 induces inflammatory mucus response in NHBEs ( Gundavarapu et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the HIV-1 patients, the R5 (CCR5-tropic) HIV-1 variants predominate over the course of infection, and the X4 (CXCR4-tropic) variants arise later ( Poon et al., 2012 ); however, nearly 22% of patients on cART principally harbor the X4 variants ( Ferrer et al., 2014 ). Moreover, a recent study indicated that X4 variants are mainly associated with pulmonary arterial hypertension—a lung condition quite prevalent among PLWH ( Almodovar et al., 2020 ). Most importantly, NHBEs explicitly express CXCR4 ( Eddleston et al., 2002 ; Gundavarapu et al., 2013 ), and the X4- but not the R5-tropic HIV-gp120 induces inflammatory mucus response in NHBEs ( Gundavarapu et al., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Once binding occurs, gp120 undergoes a conformational change, exposing coreceptors on gp120 to bind to chemokine C-X-C type 4 receptor (CXCR4) / C-C chemokine receptor 5 (CCR5) co-receptors on the host immune cells. The HIV virions which bind with CCR5 are known as R5 viruses, while those attached to CXCR4 are X4 viruses [16,18]. ECs are seemingly resistant to HIV infection [6,19] since HIV virions, HIV-DNA, p24 antigen, or HIV-RNA have not been isolated from the pulmonary ECs [7][8][9]18].…”
Section: Hiv-gp120mentioning
confidence: 99%
“…The HIV virions which bind with CCR5 are known as R5 viruses, while those attached to CXCR4 are X4 viruses [16,18]. ECs are seemingly resistant to HIV infection [6,19] since HIV virions, HIV-DNA, p24 antigen, or HIV-RNA have not been isolated from the pulmonary ECs [7][8][9]18]. However, a study performed by Sharilyn Almodovar et al confirmed the presence of co-receptors in the HPMVECs.…”
Section: Hiv-gp120mentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34][35] However, emerging evidence has demonstrated that genetic defects play a pivotal role in the pathogenesis of idiopathic PAH, especially for familial PAH, and deleterious mutations in multiple genes, including BMPR2 encoding a receptor of the transforming growth factor-β superfamily, TBX4 encoding a transcription factor, and KCNK3 as well as ABCC8 encoding potassium channels, have been found to cause PAH. 1,4,[36][37][38][39][40][41][42][43][44][45][46][47] In addition, genome-wide association studies have revealed that common genetic variations are associated with an enhanced susceptibility to PAH. 48) Nevertheless, due to substantial genetic heterogeneity of PAH, the genetic determinants underpinning PAH in the overwhelming majority of patients remain to be identified.…”
mentioning
confidence: 99%